Synergistic effect of venetoclax and teglicar in multiple myeloma cell lines - Belal A. Al-Husein; Jood Hashem; Sara S. Alawi; Mohammad A. Y. Alqudah; Ahmad Al-Azayzih (Pensoft Publishers, 2024)
Multiple myeloma is a hematological malignancy characterized by the clonal proliferation of plasma cells. Recent advancements in treatment strategies have led to a significant shift in the management of this malignancy. Venetoclax, an apoptosis inducer, has emerged as a promising therapeutic option for multiple myeloma. Fatty acid oxidation (FAO) is one of the metabolic reprogramming events that occurs because of mutations in certain genes and thus plays a crucial role in cancer progression. Teglicar, a reversible inhibitor of FAO, targets carnitine palmitoyl transferase 1 (CPT1) and has shown potential in cancer treatment due to its interaction with apoptotic regulators such as Bcl-2. In this study we investigated the in vitro anti-cancer activity of teglicar, in myeloma cell lines (RPMI 8226 and U266B1). Our findings revealed a significant inhibition of RPMI 8226 cell viability with an IC50 = 50 µM, but at a higher concentration for U266B1 cells. Notably, the combination of teglicar with venetoclax showed a synergistic effect. Although both cell lines were known to be resistant to venetoclax, teglicar significantly reduced IC50 of venetoclax by 5.33 and 1.7 folds in RPMI 8226 and U266B1 respectively. In addition, single agent and combination treatment were associated with a significant increase in apoptosis in both cell lines. However, the combination therapy had no significant effect on reactive oxygen species (ROS) levels in either cell lines. Our results suggest that the combination of teglicar and venetoclax holds promise in multiple myeloma through induction of apoptosis. This study sheds light on the potential therapeutic implications of targeting FAO, specifically through CPT1 inhibition, in conjunction with apoptosis inducers for enhanced anticancer effects in multiple myeloma.